Comparative Effectiveness of PBL, PjBL, and Discovery Learning in Pesantren: Controlling for IQ - lutfi, ahmad; Sari, Alfizah Ayu Indria (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study investigates the comparative effectiveness of three instructional models—Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Discovery Learning—on students’ academic achievement while controlling for Intelligence Quotient (IQ) using ANCOVA. Conducted at Pondok Pesantren Modern Nurul Ikhlas, the study employed a quasi-experimental design involving 120 Grade X students randomly assigned to three treatment groups. IQ was measured using Raven’s Progressive Matrices and treated as a covariate. The post-test achievement scores were analyzed using ANCOVA to examine the adjusted effects of each instructional model. Results indicate that the instructional model had a statistically significant effect on student achievement (p < 0.001), with PjBL outperforming both PBL and Discovery Learning. No significant difference was found between PBL and Discovery Learning. The findings suggest that instructional strategies significantly influence learning outcomes independent of students’ cognitive abilities. Furthermore, controlling for IQ increased the internal validity of the study and provided a clearer understanding of pedagogical impact. The study contributes to the development of evidence-based instructional strategies and supports the integration of constructivist models in diverse educational settings, including faith-based institutions. These findings underscore the importance of professional development and instructional innovation in enhancing academic achievement.